Lawyers, power, and responsibility : bodyguards of lies - Whelan, Christopher (London [England] : Hart Publishing, 2022)
"This book uses real-world examples, case studies, and commentary from practitioners to reveal the many and varied strategies American and English lawyers use to protect truth. It shows how they tackle their conflicting duties, and highlights the 'tragic choices' lawyers everywhere routinely make through their 'power of decision'. What emerges are new ways of understanding the critical role lawyers play in society - and their professional responsibilities. 'Truth is so precious it should always be protected by a bodyguard of lies.' Churchill said this about wartime deception plans, but lawyers' clients may think their truth - especially an 'inconvenient truth' - is so precious it too should be protected. Lawyers are 'bodyguards of lies' when they use so-called 'tricks of the trade' not only to keep clients' secrets but to construct a reality that is far from real. But should they? Lawyers have a divided loyalty. The book presents a unique and fascinating account of what happens when lawyers' duties to clients conflict with their duties to the legal system, and looks in detail at the ethical codes and laws that regulate their conduct."--
Part A: Setting the Scene -- 1. Introduction -- 2. Justifying the Lawyer's Role - 'Hired Guns' and/or 'Heroes'? -- 3. Lawyers: A Divided Loyalty? Part B: Strategies to Protect the Truth -- 4. Keeping Confidentiality -- 5. The Lecture: Lying with the Law -- 6. The Inconvenient Truth: Selective Ignorance and Wilful Blindness -- 007. Licence to Lie -- 8. Exploring Outer Space and the Limits of Law -- 9. Creative Compliance: Legal Means Ethical -- 10. The Sword of Truth and the Dagger of Deceit - Lying with the Truth -- 11. The Smoking Gun -- 12. A Sporting Chance: Courtroom Tactics in a Criminal Context -- 13. Effective Advocacy -- 14. Courting the Court of Public Opinion Part C: Bodyguard Ethics -- 15. The Slippery Slope? -- 16. Ethical Discretion Part D: Conclusion -- 17. The Power and Responsibility of Lawyers as Bodyguards of Lies
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Legal ethics -- England; Legal ethics -- United States; Practice of law -- Moral and ethical aspects -- England; Practice of law -- Moral and ethical aspects -- United States; Electronic books